A Formal Classification of Dialogue Units - Vilkienė, Loreta (Kalbotyra, 2000)
The elementary dialogue unit is a cycle which presents a complex of replications bound by certain relations. In it both replications of verbal expression and those of body language are considered equivalent. The present article is based on “Svečias” (The Guest), a novel by Vytautas Bubnys. The following structural models of cycles were singled out: 1. Binomials: St → Re. These are the most often produced dialogue cycles when a speaker’s (St) communicative intention is asserted, to which a dialogue partner (Re) correspondingly reacts. 2. Trinomials: a) St → Re → C; i.e. stimulus - reaction - comment, by which an observation on both reaction and stimulus can be made. b) In → St → Re: introduction - stimulus - reaction. Replication-introduction presents certain matters of context. Then stimulus narrows the theme set out in the introduction section and puts a question which is answered by reaction. 3. Fournomials: St1 → (St2 → Re3) → Re1: stimulus St1 formulated by the addresser which he or she later specifics by stimulus St2. Then communicant Re2 responds to the latter stimulus and only then reaction Re1 is produced to the first stimulus. 4. Fivenomials: St1 → (St2 → Re2) → Re1: it looks as if it were a fournomial cycle supplemented by comment C of replication Re1. 5. Sixnomials: St1 → (St2 → Re2) → (St3 → Re3) → Re1: they are structured in a similar manner as fournomial cycles do; only one more pair of replications appears. 6. Monomials: St → Re = 0: i.e. there is no reaction towards verbal stimulus because the addressee of the dialogue for some reasons does not wish to respond or does not understand the stimulus.